Makna Kata Kerajaan Bahasa Melayu: Satu Analisis Komponen Dan Parafrasa - Ikhsan, Jamilah (1996)

(untitled)
This thesis analyses the lexical meaning, function and dynamic usage of verbals in Malay. Verbals in this context cover adjectives and real verbs. Verbals are choosen for this study because verbals (whether it has undergone affixation or not) is a major gramatical category and is widely used. In fact, verbals are the core elements in the Malay sentence constructions.The model used in the study is the componential analyses of Katz and Fodor (1963) and the paraphrase method of Znhnrin Yusoff (1989).